Pengaruh Lingkungan Kerja dan Motivasi Kerja terhadap Kinerja Karyawan Crew Burger King Surabaya Timur - Indiargo Dwi Prastyo; Bowo Santoso (Research and Strategic Studies Center (Pusat Riset dan Kajian Strategis) Fakultas Syariah IAI Nasional Laa Roiba, 2022)
To achieve a company goal, its important to looking for employee performance, work environment, and work motivation. Good or bad employee performance can be influenced by the work environment and motivation, as well as the Burger King company in East Surabaya. Burger King Company is a company engaged in FnB. This study aims to analyze the effect of work environment and work motivation on employee performance of Burger King East Surabaya crew. The hypothesis in this study is that the work environment and work motivation have a significant influence on employee performance. This study uses quantitative methods and uses PLS as a test tool as well as data collection methods by conducting surveys. Respondents in this study were 50 respondents using a saturated sampling technique where all populations were sampled. The results of the study revealed that th e work environment partially had no significant effect and work motivation had a significant positive effect on employee performance. Keywords: Work Environment, Work Motivation, Employee Performance